Pengaruh Iklim Sekolah Terhadap Kinerja Guru di SMP Negeri 1 Ulaweng Kabupaten Bone - Ilmi Sawianti; Musdalifah Musdalifah; Susdiyanto Susdiyanto (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2019)
This research discusses the influence of school climate on the teacher’s performance at Public Junior High School 1 Ulaweng, Bone Regency. It aims to: 1) Describe the actual school climate; 2) Describe the actual teacher’s performance ; 3) examine the influence of school climate on teacher’s performance at Public Junior High School 1 Ulaweng, Bone Regency. This research uses quantitative methodology with ex post facto. the samples of this research are 29 teachers of Public Junior High School 1 Ulaweng, Bone Regency. The data were collected using questionnaires and visual documentations, and then were analysed using product moment correlation coefficient, simple linear regression, as well correlation. The data analysis indicates that: 1) the actual school climate is in conducive category with score of 73% ; 2) the favourable score of the actual teacher’s performance with 70% score; 3) a positive influence of school climate on teachers’ performance, signified by 20% score with coefficient correlation value of 0,0447 and regression equation value of Y=60,734 + 0,156X.